PP.40.06: RENAL ARTERY ANATOMY AFFECTS THE BLOOD PRESSURE RESPONSE TO RENAL DENERVATION IN PATIENTS WITH RESISTANT HYPERTENSION. (June 2015) - Hering, D.; Marusic, P.; Walton, A.; Duval, J.; Head, G.A.; Esler, M.; Schlaich, M.P.
Abstract : Objective: Renal denervation (RDN) decreases blood pressure (BP), muscle sympathetic nerve activity (MSNA) and attenuates hypertension-induced organ damage in patients with resistant hypertension (RH) and bilateral single renal arteries. The BP response to RDN and safety of RDN in patients with multiple renal arteries remains unclear. Design and method: This study examined office and 24-hour BP at baseline, 3 and 6 months following RDN in 91 patients with RH including 65 patients with single renal arteries bilaterally (Group 1), 16 patients with dual renal arteries on either one or both sides (Group 2) and 10 patients with other anatomical constellations (Group 3). Thirty nine out of 91 patients completed MSNA at baseline and follow-up. Results: RDN significantly decreased office and daytime SBP in group 1 at 3 and 6 month follow-up (P < 0.001). In group 2, RDN decreased daytime SBP (P < 0.05) at 3 month follow-up. Group 3 decreased office SBP (P = 0.05), mean and night-time 24-hour SBP (P = 0.04) from baseline to follow-up. When patients in group 2 with dual renal arteries on either sides were categorized according to the left or right sides, there was a reduction in daytime SBP at 3 (P = 0.006) and 6 months (P = 0.02) post procedure in patients with dual renal arteries on the left and single renal artery on the right sides. A patient who received RDN in all 3 arteries (two right renal arteries, single left renal artery) substantially improved BP control. RDN significantly reduced MSNA in group 1 (P < 0.05) and individuals in group 3 but not in group 2. There was no deterioration in kidney function in either group. Conclusions: While RDN can safely be performed irrespective of the underlying renal anatomy, the presence of single renal arteries with or without structural abnormalities appears to be associated with a more pronounced BP and MSNA reduction than the presence of dual renal arteries in patients with RH. Nevertheless, when patients with dual renal arteries received RDN in all arteries there was trend towards a greater BP reduction. Insufficient sympathetic renal nerve ablation may account for these differences.